Utilization of Shredded Rubber Tires for Cement-Stabilized Soft Clays - Shahin, Mohamed; Hong, Liao S. (American Society of Civil Engineers, 2010)
Tire-soil mixtures can be used as good construction materials in many geotechnical engineering applications such as pavement foundations, lightweight fill in road embankments and lightweight backfill behind retaining walls. This paper describes research undertaken to investigate experimentally the impact of shredded rubber tires as reinforcing material on the mechanical properties of cement-stabilized soft clay, in terms of strength and stiffness. A series of laboratory experiments are carried out on cement-stabilized clay mixed with several portions of shredded rubber tires of sizes 440 m and 4 mm. The tests conducted include compaction, unconfmed compression strength and indirect tensile strength. The results demonstrate that the use of shredded rubber tires has a potential in enhancing the ductility of cement-stabilized soft clay but decreases stiffness and ultimate resistance.